Evaluation of the Effect of Prazosin Treatment on alpha-2c Adrenoceptor and Apoptosis Protein Levels in the Predator Scent-Induced Rat Model of Post-Traumatic Stress Disorder - GÖREN, MEHMET ZAFER (HUMANA PRESS INC, 2020)
The predator scent-induced (PSI) stress model is a rat model used to mimic post-traumatic stress disorder (PTSD) symptoms in humans. There is growing evidence that prazosin, which blocks alpha-1 and is approved by the FDA as an anti-hypertensive drug, can potentially be of use in the treatment of PTSD-related sleep disorders. The aim of this study was to investigate the role of prazosin treatment on behavioral parameters (freezing time, total transitions, and rearing frequency measured from the open field; anxiety index, total entries and time spent in open arms calculated from the elevated plus maze), apoptotic proteins and alpha-2c-AR in fear memory reconsolidation in the PSI stress rat model. We used western blot analysis to determine the effect of prazosin (0.5 mg/kg/ip) on alpha-2c-AR and apoptotic protein expression changes in the frontal cortex, hippocampus, and amygdala. It was determined that in the stress group, there was increased freezing time and anxiety index, and decreased rearing frequency, total transitions, total entries, and time spent in open arms compared to the control groups. Following PSI-stress, pro-apoptotic (bax) protein expression levels increased and alpha-2c AR and anti-apoptotic protein (bcl-2) levels decreased in investigated all brain regions. The majority of stress-induced changes were recovered with prazosin treatment. The results of our study may potentially be useful in understanding the effect of prazosin treatment, given the fact that the amygdala, frontal cortex, and hippocampus regions are affected for stress conditions.
Keywords: alpha-2c adrenoceptor; Apoptosis; bcl-2; Prazosin; Post-traumatic stress disorder; CONDITIONED FEAR; BRAIN-REGIONS; ANIMAL-MODEL; OPEN-FIELD; ANXIETY; EXTINCTION; BEHAVIOR; PHARMACOTHERAPY; PROPRANOLOL; ANTAGONIST